Clinical characteristics and outcomes of spontaneous bacterial peritonitis caused by Enterobacter species versus Escherichia coli: a matched case-control study. Issue 1 (December 2016) - Bae, Seongman; Kim, Taeeun; Kim, Min-Chul; Chong, Yong; Kim, Sung-Han; Sung, Heungsup; Lim, Young-Suk; Lee, Sang-Oh; Kim, Mi-Na; Kim, Yang; Woo, Jun; Choi, Sang-Ho
Abstract Background Enterobacter species are important nosocomial pathogens, and there is growing concern about their ability to develop resistance during antimicrobial therapy. However, few data are available on the clinical characteristics and outcomes ofEnterobacter spontaneous bacterial peritonitis (SBP). Methods We retrospectively identified all patients with SBP caused byEnterobacter species admitted to a tertiary care hospital between January 1997 and December 2013. Each case was age- and sex-matched with four patients withEscherichia coli SBP. Results A total of 32 cases withEnterobacter SBP and 128 controls withE. coli SBP were included. Twenty-one (65.6 %) cases and 111 (86.7 %) controls had Child-Pugh class C (P  = 0.006). Cases were significantly more likely to have hepatocellular carcinoma (65.6 % vs. 37.5 %, P  = 0.004) and upper gastrointestinal bleeding (28.1 % vs. 9.4 %, P  = 0.005). The initial response to empirical therapy (81.3 % vs. 81.2 %, P  = 0.995) and the 30-day mortality (37.5 % vs. 28.9 %, P  = 0.35) were not significantly different between the groups. Drug resistance emerged in one case and in no controls (4.3 % [1/23] vs. 0 % [0/98], P  = 0.19). Conclusions Compared withE. coli SBP, patients withEnterobacter SBP more frequently had hepatocellular carcinoma and upper gastrointestinal bleeding, yet clinical outcomes were comparable. Development of resistance during third-generation cephalosporin therapy was infrequent in patients withEnterobacter SBP.